Morphology Study of the Corrosion Rate on Weld Joint of Double Side Friction Stir Welding Aluminum Alloy AA6061 - Simonne Andrean Crisdion; Poppy Puspitasari; Avita Ayu Permanasari; Danang Priyasudana; Diki Dwi Pramono; Majid Niaz Akhtar (University of Merdeka Malang, 2023)
DSFSW welding uses the rotating of a tool in the workpiece to create heat owing to friction between workpiece and tool to be connected. Corrosion is influenced by the presence of high heat owing to friction and a non-uniform cooling rate. The heat transforms the metal in the Heat Affected Zone (HAZ) and Weld Metal (WM) region, which can result in flaws such porosity, kissing bond, fractures, voids (from welding penetration), and flash as well as changes to the microstructure. Changes in the microstructure of welded joints can affect the resistance of welded joints to corrosion. The purpose of this study is to experimentally analyze the main causes of failure of AA6061 DSFSW joints based on welding temperature, weld defects, microstructure, corrosion rate and morphology of the corroded surface. Temperature testing using thermocouple to analyze the temperature, welding joint defects using DSLR camera and radiography test, microstructure using optical microscope, corrosion rate using AUTOLAB PGSTAT and morphology of corroded surface using SEM. The temperature analysis results show that the advancing side has a higher temperature than the retreating side, due to friction between the tool and base metal accompanied by the opposite welding direction. Visual inspection shows that all specimens and welding positions produce flash that is quite rough on the top (1G) and bottom (4G) surfaces and radiographic test results show incomplete fusion in 4 specimens. Microstructure shows a change in shape and size resulting in recrystallization in the form of fine grains. The highest corrosion rate is found in specimen B 1G welding position of 0.63856mm/year and the lowest corrosion rate in specimen A of 0.058567mm/year. SEM test results show the type of corrosion that occurs in DSFSW welding joints is pitting corrosion.